STEM-Based e-LKPD Development in Islamic Context to Enhance Creative Thinking in Digestive Studies - Khintan Maharani Subhana Yass Padh; Zulfiani Zulfiani; Ahmad Sofyan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to produce teaching materials in Electronic Student Worksheets (E-LKPD) based on STEM in an Islamic context to improve creative thinking skills in the human digestive system. The development process involved validity testing by six experts, readability testing by 18 students, and field trials by one biology teacher and 36 students. The study results indicate that the developed E-LKPD is highly valid and effective. The E-LKPD achieved an average validity rating of 90.87%, classified as feasible. Regarding readability, it scored an average of 98.84%, indicating it is highly appropriate for users. Furthermore, field trials revealed positive feedback from teachers and students, with feasibility ratings of 91.26% and 98.49%, respectively, confirming that the E-LKPD is very well-received and effective in practical use. There is an increase in the average ability to think creatively as measured through test instruments. The study significantly enhances students' creative thinking abilities by implementing E-LKPD. Before using E-LKPD, the average creative thinking score was 34.86, which increased to 72.08 after implementation, with an N-Gain of 0.55, categorized as medium. These results demonstrate that E-LKPD is highly suitable for learning activities and effectively improves students' creative thinking skills.